2013
DOI: 10.1530/jme-12-0148
|View full text |Cite
|
Sign up to set email alerts
|

Calcium handling in porcine coronary endothelial cells by gastrin-17

Abstract: In porcine coronary artery endothelial cells (PCAEC), gastrin-17 has recently been found to increase nitric oxide (NO) production by the endothelial NO synthase (eNOS) isoform through cholecystokinin 1/2 (CCK1/2) receptors and the involvement of protein kinase A (PKA), PKC and the b 2 -adrenoreceptor-related pathway. As eNOS is the Ca 2C -dependent isoform of the enzyme, we aimed to examine the effects of gastrin-17 on Ca 2C movements.Thus, experiments were performed in Fura-2-acetoxymethyl-ester-loaded PCAEC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…39 Our finding that progastrin also binds to the CCK2R was initially somewhat puzzling, since studies to date have not shown the activation of classical GPCR signaling pathways by progastrin stimulation. Thus, while numerous G protein-coupled pathways have been linked to signaling by amidated gastrin through the CCK2R, including Ca 2+ and ERK signaling, 40 we show for the first time that progastrin signals not through classical G protein-coupling, but rather through a beta-arrestin pathway. In contrast to amidated gastrin, progastrin failed to activate intracellular calcium fluxes, a classical measure of Gq-mediated activation of protein kinase C. Furthermore, progastrin-dependent proliferation was blocked by siRNAs directed against beta-arrestin 1 and 2.…”
Section: Discussionmentioning
confidence: 64%
“…39 Our finding that progastrin also binds to the CCK2R was initially somewhat puzzling, since studies to date have not shown the activation of classical GPCR signaling pathways by progastrin stimulation. Thus, while numerous G protein-coupled pathways have been linked to signaling by amidated gastrin through the CCK2R, including Ca 2+ and ERK signaling, 40 we show for the first time that progastrin signals not through classical G protein-coupling, but rather through a beta-arrestin pathway. In contrast to amidated gastrin, progastrin failed to activate intracellular calcium fluxes, a classical measure of Gq-mediated activation of protein kinase C. Furthermore, progastrin-dependent proliferation was blocked by siRNAs directed against beta-arrestin 1 and 2.…”
Section: Discussionmentioning
confidence: 64%
“…The gastrin peptide family has two subtype receptors, namely, CCK 1 R and CCK 2 R. The expression of CCK 2 R is greater than CCK 1 R in the coronary arteries and has a higher affinity for gastrin than CCK 1 R (Grossini et al 2013 ). Gastrin has been reported to up-regulate NO production in the artery, and the intracoronary infusion of gastrin significantly increased coronary blood flow through stimulating CCK 2 R in pigs (Grossini et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gastrin is expressed in the heart and blood vessels (Gersl et al 1981 ; Grossini et al 2011 ). Two different studies reported that gastrin promoted a transient increase of Ca 2+ (Grossini et al 2013 ) and up-regulated nitric oxide production in porcine coronary artery endothelial cells (Grossini et al 2012 ). Moreover, another study showed that gastrin increased coronary blood flow and myocardial contractility, dose-dependently, through intracoronary infusion in anesthetized pigs (Grossini et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…). [14][15][16] The fluorescence intensities obtained were corrected for cell autofluorescence at the wavelengths employed. [16] The results obtained were examined through one-way ANOVA followed by Newman-Keuls post hoc test.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of (Ca 2+ ) c was conventionally obtained by measuring the Fura-2/AM fluorescence in Ca 2+ -free (0.1 M EGTA) and Ca 2+ -saturated conditions by the equation (Ca 2+ ) c = K d ([ R − R min ]/[ R max − R ]). [ 14 15 16 ] The fluorescence intensities obtained were corrected for cell autofluorescence at the wavelengths employed. [ 16 ]…”
Section: Methodsmentioning
confidence: 99%